Effects of alternating unilateral vs. bilateral resistance training on sprint and endurance cycling performance in trained endurance athletes: A3-armed, randomized, controlled, pilot trial - Ji, S.; Donath, L.: Wahl, P. (The Journal of Strength and Conditioning Research, 2022)
Traditional preparatory resistance training for cyclists mainly relies on simultaneous bilateral movement patterns. This lack of movement specificity may impede transfer effects to specific aerobic and anaerobic requirements on the bike. Hence, this study investigated the effects of resistance training in alternating unilateral vs. simultaneous bilateral movement pattern on strength and anaerobic as well as aerobic cycling performance indices. Twenty-four trained triathletes and cyclists (age: 31.1 ± 8.1 years; Vo2max: 57.6 ± 7.1 ml·min-1·kg-1) were randomly assigned to either an alternating unilateral (AUL), a simultaneous bilateral (BIL) training group or a control group (CON). Ten weeks of resistance training (4 × 4-10 repetition maximum) were completed by both training groups, although CON maintained their usual training regimen without resistance training. Maximal strength was tested during isometric leg extension, leg curl, and leg press in both unilateral and bilateral conditions. To compare the transfer effects of the training groups, determinants of cycling performance and time to exhaustion at 105% of the estimated anaerobic threshold were examined. Maximal leg strength notably increased in both training groups (BIL: ~28%; AUL: ~27%; p < 0.01) but not in CON (~6%; p > 0.54). A significant improvement in cycling time trial performance was also observed in both training groups (AUL: 67%; BIL: 43%; p < 0.05) but not for CON (37%; p = 0.43). Bilateral group exhibited an improved cycling economy at submaximal intensities (~8%; p < 0.05) but no changes occurred in AUL and CON (~3%; p > 0.24). While sprint cycling performance decreased in CON (peak power: -6%; acceleration index: -15%; p < 0.05), improvement in favor of AUL was observed for acceleration abilities during maximal sprinting (20%; d = 0.5). Our pilot data underpin the importance of resistance training independent of its specific movement pattern both for improving the endurance cycling performance and maximal leg strength. Further research should corroborate our preliminary findings on whether sprint cycling benefits favorably from AUL resistance training.